CREATIVE THINKING AS A PSYCHOLOGICAL FACTOR DETERMINING STUDENTS' LEARNING CHARACTERISTICS (Web of Teachers: Inderscience Research, 2023)
In the article, students are considered as future specialists, the theoretical issues of creative thinking and creativity formation in them were clarified, and experimental data were presented.